Territórios assombrados da extração : penetrando na mina planetária - Paoli, Eleonora (2022)
This dissertation aims, through a trans-scalar cartographic approach, to identify and analyse the damage to mining territories and their communities caused by mineral extraction. Since this economic activity is responsible for making the territory vulnerable at different scales, the work intends to demonstrate that what haunts these territories is not restricted to specific occurrences of dam failure or risk of dam failure, but is also revealed through a concatenation of predatory actions and practices that are often invisible. To better illustrate this process that covers the planetary scale of the mine, this dissertation aims to identify how the haunting occurred in a reference case, in the town of Barão de Cocais-MG, whose communities are exposed to the risk of failure of the Sul Superior and Sul Inferior dams, owned by Vale. As a result, the method of critical cartography, based on reports from representatives of communities and social movements, allowed the representation of the damages of this haunted territory. This intends to encourage the unveiling of slow and invisible violence and the claim for compensation for the damages of those affected, since this is not an isolated case, but a model of a reality that is increasingly recurring.